The Development of Pre-Service Teachers’ Teaching Performance in the Teaching Practice Program at English Department of State Islamic University of Antasari Banjarmasin - Mufidah, Nida (Dinamika Ilmu, 2019)
Teacher’s professional development is a long journey and it should be started from the college. The present paper discusses the development of pre-service teachers’ teaching performance at English department of State Islamic University of Antasari Banjarmasin when they were participating in the teaching practice program. It elaborates what they had done in the program and how their performance improved week by week. There were ten pre-service teachers who became the subjects of this report. The writer recorded their teaching techniques, media, and some feedbacks in a field note. An interview was also conducted to better understand their personal self-reflection on what they have achieved and to figure out their problems in teaching. The result of the study shows that the teaching practice program helped the pre-service teacher to develop their teaching performance by getting the feedback from the supervisor. The students’ ability to plan a lesson was improved week by week. They knew how to structure the lesson and write good lesson plan. In explaining the lesson, some common problems located on their pronunciation and grammar skills. Some also needed to know the way to manage and engage the students, and to close the lesson. The Pre-service teachers were able to use various media but they need to have better preparation to use them. In term of method used, CA, GTM, and ALM were commons method used by the students to teach various topics/ skills.